Bond Strength Deterioration of Reinforced and Prestressed Concrete Members at Reversed Cyclic Loads - Lee, J.-Y.; Kim, K.-H.; Kim, S.-W.; Choi, H. (Проблемы прочности, 2015)
The bond strength of concrete members at reversed cyclic loads is quite different from that of the concrete members at monotonic loads. Reversed cyclic loads produce a progressive bond deterioration that can lead to failure at cyclic stress levels lower than the ultimate stress at monotonic loads. In addition, the structural behavior of concrete members at dominant reversed loads reveals a dramatic reduction of energy dissipation in the hysteresis region due to a severe pinch effect. A method was proposed to predict the structural behavior of concrete members failing in bond after flexural yielding. The method takes into account the bond deterioration due to the degradation of concrete in the postyield range. To verify the bond behavior by the proposed method, predicted results were compared with the experimental data for concrete members at reversed cyclic loads, cited in the literature. Comparison of the experimental and calculated bond behavior of examined concrete members showed reasonable agreement.